Development of an algorithm for fast corner points detection - Verkeenko, M. S. (Journal of computer & systems sciences international, 2014)
A method for detecting corner points in digital images is presented. The method is distinguished by high stability and efficiency compared with many method for detecting corner points developed earlier. The stability of corner detection is especially important in computer vision tasks connected with matching images of the same object, recovering digital surface models based on a set of images, and tracking objects. The overwhelming majority of algorithms detect equally well both correct corners and excessive points not corresponding to real corners of objects. The presented algorithm does have this disadvantage, and it can be used in frame-to-frame processing video in real time, e.g. in navigation systems of mobile robots and unmanned aerial vehicles. In addition, the proposed algorithm may be adapted to any data set since it is based on the machine learning method. The advantages of the developed method are demonstrated by an example of detection of corners in images of a typical hangar and in images with the international space station.